CIE 1931 colour space movement of organic light emitting diode - Woon, Kai Lin (National Institute of Optoelectronics, 2010)
2x2 Transfer Matrix modelling is used in order to study the movement of colour point in CIE 1931 colour space. Simulation indicates that increasing the thickness of light emitting layer shifts the CIE 1931 colour space towards the red in a linear fashion until a critical inflexion point. Beyond that point, the colour point reverses in direction. The colour points trace out small circular track by changing the thickness of indium tin oxide and poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate). Higher injection cathode is found to red-shift the colour of the OLED. Increasing the concentration of red-emission shifts the CIE coordinate linearly.